The Impact of Competency that Result From Organizational Motivation, Compensation and Climate on Employee Performance - Maulidah, Khofifah (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
High employee competence will be encouraged to work hard by utilizing the abilities and skills they have ultimately impact on the performance of each employee. With this research objective is to determine the effect of motivation, compensation and organizational climate on employee performance compensation. So with this the positivism philosophy method is used, with a total sample of 226 employees. In this study the analysis used was multiple linear regression, using survey research techniques. To determine the results of this study, descriptive analysis, validity test, reliability test, normality test, multicollinearity test and heteroscedasticity test are needed to determine the results. The results of this study indicate that motivation, compensation and organizational climate simultaneously have a positive and significant effect on employee performance competencies